Soil Moisture Control System for Lettuce Seeds: Time-based Alternative Approach - Fakhruddin Mangkusasmito; Ageng Rilla Aldonanda; Dista Yoel Tadeus (Faculty of Engineering and Informatics, Universitas Multimedia Nusantara, 2023)
The utilization of lettuce leaves as a nutritious dish has made its demand relatively high. This research presents a moisture control method to optimize seed growth for lettuce. The prototype system has been developed using Arduino Mega, DF Robot soil moisture humidity sensor, and DC spraying pump for testing three different control scenarios, the open loop control system (time-based), the Proportional control system, and the combination of open loop and Proportional control method as an alternative. The results show that each control method can achieved the desired moisture of rockwool at 60%. Also, the combination of open loop and Proportional control can lessen energy usage of the system by up to 51% compared to the common open loop method.